2020
DOI: 10.7759/cureus.9315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ventricular and Lumbar Cerebrospinal Fluid Composition

Abstract: Cerebrospinal fluid (CSF) analysis is a common diagnostic tool used to evaluate diseases of the central nervous system (CNS). We sought to determine whether there is a difference between the composition of CSF sampled from an external ventricular drain (EVD) and lumbar drain (LD) and whether this made a difference in guiding therapeutic decisions. Patients and Methods This study was a retrospective analysis from a single neurosurgery service between the dates of January 2011 and April 2019. A total of 12,134 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Previous research and case studies have found cellularity to be increased in lumbar CSF compared to ventricular CSF [33][34][35][36]. Additionally, both Podkovik et al and Gerber et al noted the risk of these findings impacting early infection diagnostics [34,35].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research and case studies have found cellularity to be increased in lumbar CSF compared to ventricular CSF [33][34][35][36]. Additionally, both Podkovik et al and Gerber et al noted the risk of these findings impacting early infection diagnostics [34,35].…”
Section: Discussionmentioning
confidence: 98%
“…Previous research and case studies have found cellularity to be increased in lumbar CSF compared to ventricular CSF [33][34][35][36]. Additionally, both Podkovik et al and Gerber et al noted the risk of these findings impacting early infection diagnostics [34,35]. As a sedimentation effect that may impact clinical decision making have been demonstrated for the lumbar versus the ventricular region, it is somewhat surprising that the local sedimentation effect in the ventricles have not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the comparison between TBI and controls could be somewhat biased considering the location of the CSF collection. Whereas the TBI patients had their CSF samples collected from external ventricular drains, controls had a lumbar puncture for CSF collection, which could affect the composition and content of various purines and their metabolites (Brandner et al, 2013; Hegen et al, 2018; Podkovik et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the TBI patients had their CSF samples collected from external ventricular drains, controls had lumbar puncture for CSF collection, which could affect the composition and content of various metabolites though a specific influence on purines is not known yet (Brandner et al, 2013;Hegen et al, 2018;Podkovik et al, 2020).…”
Section: Discussionmentioning
confidence: 99%